Performance and power management of droplets-based electricity generators. (February 2022) - Li, Xuemei; Ning, Xiaoyu; Li, Luxian; Wang, Xiang; Li, Baowen; Li, Jidong; Yin, Jun; Guo, Wanlin
Abstract: Harvesting energy from raindrops has attracted extensive efforts due to the wide distribution of precipitation and vast potential applications. Among the various approaches developed for this purpose, droplets-based electricity generators (DEGs) based on electrostatic induction have been becoming an outstanding option in the aspect of output voltage and instantaneous power density. Performance dependence of DEGs on the device configuration and the dominating factors have to be revealed for the further optimization. Here, we comprehensively investigated the performance of DEGs with three different configurations, i.e ., bottom-electrode, top-electrode and double-electrode, and found that water-to-ground capacitance played an important role in determining the device output. Besides, the conductivity of water shows notable influence on the device performance, tap water with a conductivity around 300 μS/cm shows the highest efficiency in our measurements. Adapting an optimized power management circuit, the pulsed-like output of DEGs is converted to a constant voltage output of variable amplitudes, which is successfully used to charge a smart phone. Our results shed light on possible ways to further optimize the DEG configuration and their potential applications. Graphical Abstract: ga1 Highlights: Increasing water-to-ground capacitance boosts the device output. Water with lower conductivity gives rise to a longer electrical relaxing time and thus a wide pulse. Connecting an inductor in series with a capacitor in the power management circuit improve the circuit efficiency. Charging a smartphone using the device with the optimized power management circuit is demonstrated.